COVID-19 Pandemic and Blended Learning: A Quantitative Assessment of Revised Community of Inquiry (RCoI) Framework (Journal of Education and Educational Development, 2021)
This paper presents the Revised Community of Inquiry (RCoI) framework to identify different aspects of learning presence (Learner, Teaching, Social and Cognitive presence) in a blended learning course. RCoI framework emphasizes on the roles of stakeholders in online education. This research tested the impact of RCoI on Students Learning with the moderating role of Technology (Learning Management System). The data was collected from 462 students in different universities in Karachi, Pakistan. Results identified that there is a positive relationship of RCoI and Technology Use (LMS) on Students Learning in a Blended/Hybrid course. Further, there was one moderating role of technology Use (LMS) found in this research. Technology moderates the relationship between Cognitive presence and Students Learning. It shows that technology reduces the cognitive presence of students and reduces their effective learning. They are lesser involved in critical thinking and problem solving as compared to classroom teaching.